Barotrauma may be a specially relevant concern in COVID-19 ventilated patients - Alves, Adelaide; Romano, Carolina; Fonseca, Tatiana; Pipa, Sara (Journal of the Portuguese Society of Anesthesiology, 2021)
Invasive mechanical ventilation plays a key role in the management of respiratory failure induced by SARS-CoV-2 infection. Patients with COVID-19 have been associated with need for both long periods of ventilation and higher pressures applied to a often damaged lung parenchyma. These features may prompt an increased risk of lung injury, namely barotrauma, even when a lung protective ventilation strategy is applied. We report a case of a COVID-19 ventilated patient who developed several barotrauma related complications that ultimately led to death.